The relationship between Eastern Cooperative Oncology Group performance status and healthcare resource utilization among patients with advanced or metastatic colorectal, lung or gastric cancer. Issue 1 (25th April 2021) - Hess, Lisa M.; Smith, David; Cui, Zhanglin L.; Montejano, Leslie; Liepa, Astra M.; Schelman, William; Bowman, Lee
Abstract: Aims: The ability of a patient to receive anti-cancer treatment depends on a variety of factors, including performance status (PS), which is typically measured using the Eastern Cooperative Oncology Group (ECOG) scale. This study hypothesized that there would be a strong and positive correlation between ECOG PS values and healthcare resource utilization (HCRU) and a strong and negative correlation with the use of anti-cancer therapy. Materials and methods: Patients with colorectal, lung or gastric cancer were included in this retrospective analysis of administrative claims data linked to electronic medical records (EMR). All-cause HCRU (hospitalization/inpatient care, emergency room visits, systemic anti-cancer therapy, radiation therapy, outpatient physician visits, hospice, home health care and key supportive care treatments such as anti-emetics, hematopoietic treatments, transfusions, and durable medical equipment) was evaluated by baseline ECOG PS value and PS over time. Adjusted multivariable regression analysis was used to assess the relationship between baseline ECOG PS and HCRU. Regression analyses were conducted to explore the relationship between other baseline variables and HCRU. Results: There were 1311 patients included in this study. There was low correlation between PS and any HCRU variable or receipt of anti-cancer therapy (correlation coefficients all <0.10). In regression analyses, the proportion of patients with poor PS (PS = 2+) who were hospitalized was not significantly different from those with good PS (PS = 0/1) (28.9% versus 19.3%, p  = .07). Limitations: The low rate of reporting of PS and the small sample size of patient groups in this study. Conclusions: There is very little evidence of a relationship between ECOG PS and HCRU, ECOG PS, or anti-cancer therapy in this study, in part due to low rates of and lack of variability in reported PS. There is some evidence that baseline comorbidities were significantly associated with HCRU and should be accounted for in future research evaluating HCRU.